2006
DOI: 10.22230/cjc.2006v31n4a1795
|View full text |Cite
|
Sign up to set email alerts
|

Virtually Queer? Homing Devices, Mobility, and Un/Belongings

Abstract: This article counters and complicates decontextualized, celebratory accounts of queer subjects and cyberspace. The authors explore the significance of communicative media for queer women, with a particular focus on the negotiation of complex identifications, communities, social networks, and knowledge practices. Using a critical, sociocultural approach, the authors make illustrative use of interviews conducted in British Columbia and Alberta that are part of an ongoing research project (www.queerville.ca) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…He proceeds to explore a range of gender issues from comparisons of male and female Internet use and the participation of males and females in games, onlinelearning situations, e-mail interactions, blogs, chat rooms, and other sites as he discusses issues of power, identity construction, impersonation, affiliation, and agency. However, he seems to understate the dynamic and complex nature of these spaces and how individuals and groups are or are not located and displaced by them via blogs, chat rooms, listservs, or a combination of online or offline spaces (see Bryson, MacIntosh, Jordan, & Lin, 2006).…”
Section: Part Iii: Communicationmentioning
confidence: 99%
“…He proceeds to explore a range of gender issues from comparisons of male and female Internet use and the participation of males and females in games, onlinelearning situations, e-mail interactions, blogs, chat rooms, and other sites as he discusses issues of power, identity construction, impersonation, affiliation, and agency. However, he seems to understate the dynamic and complex nature of these spaces and how individuals and groups are or are not located and displaced by them via blogs, chat rooms, listservs, or a combination of online or offline spaces (see Bryson, MacIntosh, Jordan, & Lin, 2006).…”
Section: Part Iii: Communicationmentioning
confidence: 99%
“…Francisco as homelands to which rural and small-town gay men and lesbians moved as they sought out queer compatriots and a stake in the United States' emergent gay rights movement. Interestingly, framings of queer migration as a phenomenon based on national and regional oppositions have persisted despite an increasingly connected world (Munt et al 2002;Bryson et al 2006) and more inclusive (yet still uneven) regimes of queer rights in North America (Lind 2004;Smith 2005a).…”
Section: Queer Migration In the North American Imaginarymentioning
confidence: 99%
“…Reflecting on their past migrations, some men suggested that volunteering and advocacy had once been dominant modes of both identifying oneself as gay and engaging with the community. While moving out was thus more of an imperative for young gay men in the 1980s, the advent of the internet and a decline in advocacy in the 1990s and later rendered relocation perhaps a less obvious-but still common-life choice (see also Munt et al 2002;Bryson et al 2006).…”
Section: Changing Historical Contingenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scene from the L Word, Angry Gay is replaced with Fun Gay in a classic neoliberal displacement of a politics of identity with a performative politics of mediatization, consumption, and an excess of visibility (Jameson 1991;McRobbie 2005;Bryson 2004Bryson , 2005Campbell 2004;Gray 2004;Bryson et al 2006;O'Riordan and Phillips 2007;Driver 2008;MacIntosh and Bryson 2008) takes up the complex project of unthinking neoliberal accounts of a progressive modernity. Current social theory identifies in the free-market logics of neoliberalism, historically disjunctive political-economic social practices and relationalities that: (1) have effected broad changes in the technologies of governing, knowledge, and related modes of subjectivity and subjectification (Rose 1998;Ong 2006), and (2) require us to address novel ethical problems pursuant to what Nikolas Rose has termed, the 'politics of life itself' (2007,3).…”
Section: Introductionmentioning
confidence: 99%